(untitled) (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2025)
This article aims at identifying the types of derivational morphemes that can be found in a selection of songs by Will Wood as well as examining the grammatical and semantic alterations that happen in the derivational process. The data sources include four of Will Woods’ most popular songs on Spotify, including I/Me/Myself, Laplace’s Angel (Hurt People? Hurt People!), The Main Character, and 2econd 2ight 2eer (that was fun, goodbye.). The research utilizes the qualitative method and the theory of derivational morphemes as stated by O’Grady et al. (2017). The data was collected using the observation and documentation method through the techniques of recording and note-taking. The data was then analyzed using the theory from O’Grady et al. (2017), which states that there are two types of affixes in the derivational process, including suffixes and prefixes. O’Grady et al. (2017) also identifies that grammatical and semantic changes can happen during the derivational process. The results suggest that derivational suffixes occur at a greater frequency and greater variety compared to the prefixes, with only one type of derivational prefix found in the selected songs. Both grammatical and semantic change were also found within the data sources.